Prevalence of obesity, hypertension and type 2 diabetes in elderly women - DOI: 10.4025/reveducfis.v20i1.4232 - Maressa Priscila Krause; Tatiane Hallage; Cristiane Petra Miculis; Renata Selvatici Borges Januário; Mirnaluci Paulino Ribeiro Gama; Sergio Gregorio da Silva (Revista da Educação Física)
Purpose: To verify general and abdominal obesity, systemic arterial hypertension (SAH) and diabetes mellitus (DM) prevalence, and to analyze their association with general and abdominal adiposity in elderly women. Methods: Study participants were 1,040 elderly. General and abdominal adiposity were estimated by body mass index and waist circumference, respectively. SAH and DM were determined through interview. Data were analyzed using a one-way ANOVA, Chi-square e logistic regression tests. Results: The relative frequencies of abdominal obesity were significantly different among the city’s districts (x2=21.78, p